Absolute lymphocyte count is a prognostic marker in Covid‐19: A retrospective cohort review. (10th July 2020) - Wagner, Jason; DuPont, Andrew; Larson, Scott; Cash, Brooks; Farooq, Ahmad
Abstract: Introduction: Prognostic factors are needed to aid clinicians in managing Covid‐19, a respiratory illness. Lymphocytopenia has emerged as a simply obtained laboratory value that may correlate with prognosis. Methods: In this article, we perform a retrospective cohort review study on patients admitted to one academic hospital for Covid‐19 illness. We analyzed basic demographic, clinical, and laboratory data to understand the relationship between lymphocytopenia at the time of hospital admission and clinical outcomes. Results: We discovered that lymphocyte count is lower ( P  = .01) and lymphocytopenia more frequent by an odds ratio of 3.40 (95% CI: 1.06‐10.96; P =  .04) in patients admitted to the Intensive Care Unit (ICU), a marker of disease severity, relative to those who were not. We additionally find that patients with lymphocytopenia were more likely to develop an acute kidney injury (AKI), a marker of organ failure, during admission by an odds ratio of 4.29 (95% CI: 1.35‐13.57; P  = .01). Conclusion: This evidence supports the hypothesis that lymphocytopenia can be an early, useful, and easily obtained, prognostic factor in determining the clinical course and disease severity of a patient admitted to the hospital for Covid‐19.